Educação nutricional em uma proposta CTS: desafios e possibilidades - Oliveira, Fernanda Flavia de [UNIFESP] (2018)
Adequate and healthy food is a human right provided for in the Brazilian Federal Constitution. One of the ways to ensure this right is to promote a nutritional education (NE) that is conscientious. For this, nutritional education should be taught from a perspective that addresses scientific, social, historical and technological aspects. The educational approach that best favors the discussion of these aspects is ScienceTechnology-Society (STS). The objectives of this work were to elaborate, apply and evaluate a didactic sequence (DS) of seven classes with a STS approach to nutrition education. The specific objectives of the didactic sequence were: to recognize the main components of foods (carbohydrates, lipids and proteins) consumed daily; recognize the chemical properties of carbohydrates, lipids and proteins; relate the chemical properties of foods to their functions in the body; understand the interrelationship between historical, social, technological and economic factors in the composition of food patterns. In order to elaborate and evaluate DS we used an adaptation of Didactic Engineering methodology. Fifty students from the 8th grade of Elementary School II from a state school in the city of Diadema - São Paulo - Brazil participated in this research. In the first class the students discussed a story about food and longevity. In the second and third classes we investigate the eating patterns of students using the "Exploring My Food" application. In the fourth and fifth classes we discussed the origins of eating patterns with the use of the didactic resource "Storing our food". In the sixth class we held a discussion about the different techniques of food preservation. For the survey of the conceptual contents constructed during the didactic sequence we use: records of food consumption; anthropometric and food standard questionnaire; posters; post-test questionnaire; and transcripts of all classes. To evaluate the data we use content analysis. Food consumption records, questionnaires of anthropometric and dietary standards, transcripts and post-test elaborated indicated that there was a growing appropriation of knowledge on macronutrient composition of food and good eating practices. The use of the software "Exploring my diet" showed that the use of nutritional tables combined with the calculators in the software can help the student to establish their daily consumption of macronutrients and sodium and relate it to the standards established as healthy. The didactic resource "Storing our food" makes it possible to learn the sources and functions of the macronutrients in an active and critical way, by problematizing various social, historical and economic aspects that influence the choice of food. In general, the classes proposed met the initial objectives. The data obtained from the questionnaires and student statements show that there may have been an increase in the understanding of the interrelationships between food, biological needs, culture and history.